Overestimation of the abundance of sulfate-reducing bacteria in human feces by quantitative PCR targeting the Desulfovibrio 16S rRNA gene - Christophersen, Claus; Morrison, M.; Conlon, M.A. (AMER SOC MICROBIOLOGY, 2011)
The dominant genus of sulfate-reducing bacteria (SRB) in humans is Desulfovibrio, and quantitative PCR (QPCR) targeting the 16S rRNA gene is often used in assays. We show that the 16S rRNA gene assay overestimated SRB abundance in feces from 24 adults compared to QPCR assays using primers targeting two genes involved in SRB energy metabolism. © 2011, American Society for Microbiology. All Rights Reserved.